16 Identification of Structural Variants Associated with Mastitis in Holstein Dairy Cows Using Whole Genome Sequencing and RNA-sequencing. (8th October 2021) - Asselstine, Victoria; Medrano, Juan F F; Muniz, Malane M M; Cánovas, Angela
Abstract: For the dairy industry, animal welfare and economic viability are key factors in determining the long-term sustainability of the industry. One challenge in lactating dairy cows is mastitis, as there are significant costs associated with each mastitis case due to treatment, milk loss, and potential cow culling. Differentially expressed (DE) genes, DE mRNA isoforms and DE long non-coding RNA (lncRNA) candidates were previously identified by our group between healthy and mastitic samples from six Holstein dairy cows. In total, 7 candidate genes, 5 mRNA isoforms and 4 lncRNA were targeted as they play an important role due to their association with mastitis or the immune system. The aim of the current research is to identify new structural variants in the transcriptome of these previously identified potential candidates using RNA-Sequencing. These structural variants could occur in both coding and intergenic regions of the genome and potentially impact the amino acid that is transcribed, creating a new functional or non-functional protein. In addition, whole genome sequencing (WGS) analysis was performed using hair samples collected from ten Holstein dairy cows (first lactation). Five of these animals had no previous reports of mastitis and five animals had at least one report of mastitis in her lifespan. The WGS results will be used to identify additional structural variants, especially within introns, of the previously identified candidates that could cause a genetic variation in individuals and an association to their susceptibility to mastitis disease.